Tinjauan Hukum Islam Terhadap Iddah dan Ihdad Wanita Karier: (Studi Kasus Di Kecamatan Jambesari) - Alfina Wildatul Fitriyah; Mabrurotul Mahallifah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2021)
This work is the result of research that describes the application of the law described in the Quran and Al-Hadith as well as the Law of IHL in addressing the concepts of Iddahh and Ihdad for career women. Usually, a woman not only becomes a housewife, but also contributes to the family home by working outside the home. The discussion in this study aims to uncover everything related to women's freedom to carry out activities outside the home, but there are also demanding and restrictive religious prescriptions that must be informed by research. The research method used is qualitative field research with a qualitative descriptive approach. Data collection techniques are carried out by observation, interviews and documentation. To get these answers, researchers used primary and secondary data. Both data were analyzed using qualitative analysis methods. The underlying problem is career women who do not go through the period of Iddahh and Ihdad according to Islamic law. Based on research in Jambesari Hamlet, Jambesari Darussolah District, it was found that many women whose husbands died or were divorced did not know the period of Eiddahh according to Islamic teachings. They only follow the local village customs. From the above results it can be concluded that a wan.